Review of patient safety incidents and their associated factors in a Malaysia teaching hospital from 2018 to 2022 - Hasan, Suhana (2023)
Background: The healthcare sector poses a higher risk than the aviation and nuclear industries as the probability of a patient being harmed during a visit to a healthcare facility is one in 300 chances. The implementation of a patient safety incident (PSI) reporting system provides detailed knowledge on how and what harms the patient, and not only useful to manage the institutions’ internal problems but the lesson gained can be disseminated to others as lessons to prevent similar incidents in the future. Objective: This research aspires to study the reporting rates, characteristics of PSIs and the factors associated with the major outcome of PSIs in a Malaysia teaching hospital from 2018 to 2022. Methodology: The secondary data obtained from paper-based reporting forms and the hospital’s web-based electronic incident reporting (e-IR) system from a Malaysia teaching hospital were used for this cross-sectional study. A descriptive study was used to describe the characteristic of PSI and a logistic model was used to identify the factors associated with the major outcome of PSIs. Results: A total of 263 PSIs cases were reported with the highest reporting rate of 0.21 for every 1000 patient bed-day or 0.18% per admission in 2021. The highest reported PSIs based on each category were patients more than 60 years old, male patients, incidents that took place during post meridiem (PM) shift, PSIs from the surgical-based department, incidents involving patient falls and inpatients. Nurses reported the majority of PSIs and 82.9% reported PSIs were actual cases. Drug-related PSI was significantly associated with major outcomes (Adj. OR 6.600; 95% CI: 1.364, 31.930, p-value= 0.019). Conclusion: Overall reported PSI had increased after the implementation of the e-IR in 2020. However, the PSI in this teaching hospital was still underreported compared to national and global standards. Identifying and removing barriers to report PSI must be prioritised. The processes of prescribing until administering medication need to be re-evaluated to prevent future major PSIs outcomes.